Diagnosis of Pulmonary Artery Embolism: Comparison of Single-Source CT and 3rd Generation Dual-Source CT using a Dual-Energy Protocol Regarding Image Quality and Radiation Dose - Petritsch, Bernhard; Kosmala, Aleksander; Gassenmaier, Tobias; Weng, Andreas Max; Veldhoen, Simon; Kunz, Andreas Steven; Bley, Thorsten Alexander (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose To compare radiation dose, subjective and objective image quality of 3 rd generation dual-source CT (DSCT) and dual-energy CT (DECT) with conventional 64-slice single-source CT (SSCT) for pulmonary CTA. Materials and Methods 180 pulmonary CTA studies were performed in three patient cohorts of 60 patients each. Group 1: conventional SSCT 120 kV (ref.); group 2: single-energy DSCT 100 kV (ref.); group 3: DECT 90/Sn150 kV. CTDIvol, DLP, effective radiation dose were reported, and CT attenuation (HU) was measured on three central and peripheral levels. The signal-to-noise-ratio (SNR) and contrast-to-noise-ratio (CNR) were calculated. Two readers assessed subjective image quality according to a five-point scale. Results Mean CTDIvol and DLP were significantly lower in the dual-energy group compared to the SSCT group (p < 0.001 [CTDIvol]; p < 0.001 [DLP]) and the DSCT group (p = 0.003 [CTDIvol]; p = 0.003 [DLP]), respectively. The effective dose in the DECT group was 2.79 ± 0.95 mSv and significantly smaller than in the SSCT group (4.60 ± 1.68 mSv, p < 0.001) and the DSCT group (4.24 ± 2.69 mSv, p = 0.003). The SNR and CNR were significantly higher in the DSCT group (p < 0.001). Subjective image quality did not differ significantly among the three protocols and was rated good to excellent in 75 % (135/180) of cases with an inter-observer agreement of 80 %. Conclusion Dual-energy pulmonary CTA protocols of 3 rd generation dual-source scanners allow for significant reduction of radiation dose while providing excellent image quality and potential additional information by means of perfusion maps.Key Points:Citation Format
Keywords: pulmonary angiography; radiation dose; image quality; dual-source; dual-energy; pulmonary embolism